1585. Stenotrophomonas maltophilia Infections and Approaches to Treatment. (31st December 2020) - Caffrey, Aisling; Appaneal, Haley J; Lopes, Vrishali; LaPlante, Kerry
Abstract: Background: Current knowledge of the epidemiology of Stenotrophomonas maltophilia is limited to studies from several small international medical centers. Additionally, real-world approaches to treatment are not well described. Methods: We included admissions to any Veterans Affairs (VA) medical center nationally, with positive S. maltophilia cultures collected from any culture site between January 2010 and April 2019. We reviewed epidemiologic factors of clinical characteristics and treatment. Treatment was assessed by mapping out all antibiotic exposures each day, and identifying differences (heterogeneity) in the antibiotics used and duration of their use. Results: Over the study period, we identified 8, 225 hospital admissions with positive S. maltophilia cultures. Patients were older (mean age 68.2 year) and male (97.6%), with 25.8% in the intensive care and 56.1% admitted from other healthcare settings. Respiratory cultures were most common (47.4%), followed by urine (21.4%), skin and soft tissue (17.4%), and blood (5.1%). Admissions were mostly 11 days long (median), with an inpatient mortality rate of 13.9%. The median time to culture collection from admission was day 3 of the hospitalization, and the median time to culture completion was 4 days. Changes in therapy occurred before culture completion for 67.3% of admissions. Most admissions utilized different treatment approaches (antibiotic drug and duration treatment heterogeneity 89.7%), with a median of 4 changes in therapy. Fluroquinolones were utilized in 40.6% of admissions (initiated median 4 days from admission) and sulfamethoxazole/trimethoprim in 26.3% (initiated median 7 days from admission). Inpatient mortality was significantly higher among those with changes in therapy versus those without changes (15.0% vs 5.7%, p< 0.0001), and among those without changes, mortality was significantly higher with monotherapy versus combination therapy (16.2% vs 2.6%, p< 0.0001). Conclusion: Among more than 8, 000 admissions with positive S. maltophilia cultures in the VA nationally, identification of the organism and targeted therapy did not occur until 4-7 days from admission. Differences in clinical outcomes were observed among the different treatment approaches. Disclosures: Aisling Caffrey, PhD, Merck (Research Grant or Support)Pfizer (Research Grant or Support)Shionogi (Research Grant or Support) Haley J. Appaneal, PharmD, Shionogi, Inc. (Research Grant or Support) Kerry LaPlante, PharmD, Merck (Advisor or Review Panel member, Research Grant or Support)Ocean Spray Cranberries, Inc. (Research Grant or Support)Pfizer Pharmaceuticals (Research Grant or Support)Shionogi, Inc. (Research Grant or Support)